The effct of peer education on the self-efficy and mental adjustment of breast cancer patients undergoing chemotherapy (Bangladesh Journal of Medical Science, 2020)
Background: Breast cancer ranks the first common cancer in women in Iran and is the fifth mostcommon cause of death. Peer education on the self-efficacy and mental adjustment of breastcancer patients undergoing chemotherapy can contribute to their easier adaptation to the disease.This study aimed to determine the improved mental adjustment and self-efficacy for womenundergoing chemotherapy through peer education.Study Design: This study was conductedusing pre- and post-test follow up and control design approach. 70 women with breast cancerwho underwent chemotherapy in Nemazi hospital participated in this study.Method: Usingconvenient sampling, the participant were selected and randomly assigned into two groups. Theexperimental group was randomly assigned to four groups and peer education was conductedone educational session per week for 6 weeks. To assess mental adjustment and self-efficacybefore and after the study, Mini-Mental Adjustment to Cancer Scale (Mini-MAC) and Self-Efficacy Scale for Self-Management of Breast Cancer (SESSM-B) questionnaires were used.Chi-square and t-test were used to analyze the data.Results: For the experimental group, theresults showed statistically significant improvement in self-efficacy (p